2011
DOI: 10.1002/pssa.201026557
|View full text |Cite
|
Sign up to set email alerts
|

Nonalloyed ohmic contact of AlGaN/GaN HEMTs by selective area growth of single‐crystal n+‐GaN using plasma assisted molecular beam epitaxy

Abstract: Selective area growth (SAG) based on plasma assisted molecular beam epitaxy (PAMBE) was demonstrated to be effective to achieve low contact resistance for nonalloyed ohmic metals. An AlGaN/GaN high‐electron mobility transistor (HEMT) using SAG by PAMBE with nonalloyed ohmic metals and recessed drain/source structure exhibited a low specific contact resistance of 3.7 × 10−5 Ω cm2, high‐peak drain current of 604 mA/mm, and small gate leakage current of 3.4 µA. These results demonstrate that SAG by PAMBE produces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 14 publications
0
3
0
1
Order By: Relevance
“…We require a selective-area processing (SAP) technique that avoids dry etching or ion implantation induced damages and defects. Our group previously reported a plasmaassisted molecular-beam epitaxy (PAMBE) enabled selectivearea growth (SAG) process, or PAMBE-SAG, which bypasses both etching and implantation damages, and achieved record low n-type ohmic contact resistance [23]- [28]. Very recently, we demonstrated smooth p-n grid structures using this methodology [29], [30].…”
Section: B Methodsmentioning
confidence: 99%
“…We require a selective-area processing (SAP) technique that avoids dry etching or ion implantation induced damages and defects. Our group previously reported a plasmaassisted molecular-beam epitaxy (PAMBE) enabled selectivearea growth (SAG) process, or PAMBE-SAG, which bypasses both etching and implantation damages, and achieved record low n-type ohmic contact resistance [23]- [28]. Very recently, we demonstrated smooth p-n grid structures using this methodology [29], [30].…”
Section: B Methodsmentioning
confidence: 99%
“…The severe issue is the SAG interface contaminations or impurities which would act as donors in the SAG layer. For some special structures, such as SAG n + source/drain regions, 24) the donor-like impurities will be beneficial. But for the E-mode SAG AlGaN/GaN heterostructure transistors, the SAG interface and SAG epitaxial layers are a critical region for the devices.…”
Section: Initial Process Flow For Sag Recess Structurementioning
confidence: 99%
“…In our previous studies, we were able to realize SAG by PAMBE, achieving a record low contact resistivity of 1.8 × 10 −8 Ω cm 2 and much enhanced peak drain currents for both GaN MESFET and HEMT . We also demonstrated that unlike ion implantation, the damage‐free PAMBE‐SAG technique is able to suppress the buffer leakage current and improve the breakdown characteristics . Due to the simultaneous improvement of drain current and breakdown voltage, PAMBE‐SAG is most suited to fabricate high power transistors.…”
Section: Introductionmentioning
confidence: 99%